56.1k views
21 votes
Simplify the following monomials

Simplify the following monomials-example-1
User Alyawn
by
4.7k points

2 Answers

8 votes

Answer:

4) b^10

5) 15x^11y^6

6) 8y^5x + 3x

Explanation:

b^6 + b^4 = b^10 because this is multiplication. So you have to add the degrees

(3x^3y^5)(5x^8y^1) = 15x^11y^6. This is because

3 *5 = 15.

x^3 +x^8 = x^11

y^5 + y^1 = y^6.

You have to add the degrees since this is also multiplication.

(2y^2)(4xy^3) + 3x = 24y^5x^2. This is because

2 * 4 = 8

y^2 + y^3 = y^5

x + 0 = x

Therfore, it is (8y^5x) + 3x as the final answer.

User ErichBSchulz
by
4.6k points
8 votes
The first one I know for a fact is b^10
User Ye Myat Min
by
4.8k points